2018
DOI: 10.2147/copd.s170995
|View full text |Cite
|
Sign up to set email alerts
|

Burden of disease associated with a COPD eosinophilic phenotype

Abstract: PurposeBased on blood and sputum samples, up to 40% of patients with COPD have eosinophilic inflammation; however, there is little epidemiology data characterizing the health care burden within this sub-population. Given that COPD-attributable medical costs in the USA are predicted to approach $50 billion by 2020, we analyzed the effect of blood eosinophil counts and exacerbations on health care resource utilization and costs.Patients and methodsThis cross-sectional study used electronic medical records and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 19 publications
(22 reference statements)
3
23
0
Order By: Relevance
“…Data on the impact of elevated blood eosinophil counts in patients with COPD were reported in a recent cross-sectional study in the USA. Those individuals with a blood eosinophil count ≥150 cells/µL were shown to have higher all-cause and COPD-related HCRU and costs compared with those with a blood eosinophil count <150 cells/µL 24. Taken together with our results, these findings suggest that blood eosinophil counts may be a useful biomarker for assessing disease burden in patients with COPD and identifying those who may benefit from alternative treatment strategies.…”
Section: Discussionsupporting
confidence: 76%
“…Data on the impact of elevated blood eosinophil counts in patients with COPD were reported in a recent cross-sectional study in the USA. Those individuals with a blood eosinophil count ≥150 cells/µL were shown to have higher all-cause and COPD-related HCRU and costs compared with those with a blood eosinophil count <150 cells/µL 24. Taken together with our results, these findings suggest that blood eosinophil counts may be a useful biomarker for assessing disease burden in patients with COPD and identifying those who may benefit from alternative treatment strategies.…”
Section: Discussionsupporting
confidence: 76%
“…A higher rate of study outcomes in the population with the study phenotype was expected and driven by the definition of these traits, namely history of exacerbations. A recent study also reported that patients with COPD who had an eosinophil count >150 cells/µL had higher all-cause and COPD-related healthcare costs than those with an eosinophil count <150 cells/µL 33. Taken together, these results highlight the high clinical burden of illness among patients with this phenotype and suggest that these individuals have a more severe disease course than other patients with COPD who do not meet the study phenotype criteria.…”
Section: Discussionmentioning
confidence: 65%
“…11 Two recent US studies on patients with COPD have also found an increase in healthcare resource utilization with increasing eosinophil count. 12,13 This retrospective, observational database study of COPD patients spanning multiple real-world US practice settings is the first comprehensive evaluation of the association of blood eosinophil counts with health care utilization and cost outcomes reflecting current clinical practice across the US. The aims of this cohort study were to describe patient characteristics, health care utilization and cost across groups with increasing blood eosinophil counts in a broadly representative COPD patient population.…”
Section: Introductionmentioning
confidence: 99%